Visual media under the challenges of artificial intelligence: a survey studies - Al-Shimari, Alaa Makki (Al-Adab Journal, 2021)
The researcher focuses in his study on potential changes in the basic pillars of media messaging production with the challenges of artificial intelligence and its applications, such as writing media material, preparing its executive text and presenting it to the recipient, designing graphic clips, selecting and designing graphics and visual effects, including: simulation and the presentation of programs and news on satellite channels, preparing convincing news stories, new robotic colleagues in media production, making replicas of characters, “Deep fakes,” as well as the challenges of receiving augmented reality. The research consisted of three main axes as follows: The first axis: it included the theoretical and methodological framework of the research, where the researcher demonstrated the importance of research in many indicators, one of the most important of them is that among the research that addresses the most important challenges facing media workers of all kinds: * Professional. * Knowledge. * Ethical. The second axis: The researcher wrote about the media and the most important challenges of artificial intelligence. The third axis: the results of the research and their discussion, as the researcher reached many results, one of the most important of these is the necessity of having laws and regulations governing the stage of uses of artificial intelligence elements, and that artificial intelligence gives the journalist the ability to use the machine in locations, situations and times that a human journalist cannot do in the specified place and time. As well as the recommendations suggested by the researcher, which are related to the outputs and results of the research. finally, the conclusion.